A Comparative Efficacy Evaluation of Ultrasound‐Guided Pulsed Radiofrequency Treatment in the Gastrocnemius in Managing Plantar Heel Pain: A Randomized and Controlled Trial. Issue 4 (26th February 2015) - Ye, Le; Mei, Qiyong; Li, Mingli; Gu, Minghong; Ai, Zisheng; Tang, Kun; Shi, Dongping; Wu, Xiaotong; Wang, Xiangrui; Zheng, Yongjun
Abstract Objective The treatment of plantar heel pain is highly challenging. We report ultrasound‐guided pulsed radiofrequency treatment (UG‐PRF) in the gastrocnemius to treat plantar heel pain and minimize the safety issues. Design This study compared UG‐PRF with sham treatment in 100 patients with plantar heel pain. Primary outcome measures include the pain subscale of the Foot Health Status Questionnaire (FHSQ‐pain) and "first step" pain as measured on a visual analogue scale (VAS‐"first‐step" pain). The secondary outcome measures include the FHSQ‐foot function and general foot health, and health related quality of life (assessed using the Short Form‐36 questionnaire [SF‐36]). All outcomes were measured at 3 and 6 months post‐treatment. Results The results showed the efficacy of UG‐PRF in terms of pain management, as reflected by higher FHSQ‐pain score (increased by 20.0 (P < 0.0001) and 17.9 (P = 0.001) compared with the sham treatment at 3 or 6 months, respectively) and lower VAS‐"first‐step" pain (reduced by 26.1 (P < 0.0001) and 14.3 (P = 0.01) compared with the sham group at 3 or 6 months, respectively). The FHSQ‐foot function and FHSQ‐general foot health were increased by the UG‐PRF (P < 0.05, vs sham treatment at 3 or 6 months). The SF‐36 physical component score in the sham group was 10.8 (P = 0.042) and 10.4 (P = 0.044) lower than the UG‐PRF group at 3 or 6 months, respectively. No severe complications were observed. Conclusions We conclude that the UG‐PRF is both safe and efficacious in managing plantar heel pain.